2013
DOI: 10.3389/fphys.2013.00063
|View full text |Cite
|
Sign up to set email alerts
|

Caught in the thickness of brain fog: exploring the cognitive symptoms of Chronic Fatigue Syndrome

Abstract: Chronic Fatigue Syndrome (CFS) is defined as greater than 6 months of persistent fatigue that is experienced physically and cognitively. The cognitive symptoms are generally thought to be a mild cognitive impairment, but individuals with CFS subjectively describe them as “brain fog.” The impairment is not fully understood and often is described as slow thinking, difficulty focusing, confusion, lack of concentration, forgetfulness, or a haziness in thought processes. Causes of “brain fog” and mild cognitive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 77 publications
(94 reference statements)
1
78
0
3
Order By: Relevance
“…In past work, using an executive memory task in younger POTS patients, we demonstrated that POTS patients exhibit a progressive cognitive impairment during step-wise incremental orthostatic stress (36). Moreover, cognitive impairment was associated with neurovascular uncoupling (35,52) such that the normal increase in CBF after neuronal activity (functional hyperemia) was absent in POTS patients (32,52). Neurovas- We have previously shown that POTS patients experience a deficit in NO-dependent vasodilation within the peripheral microcirculation, linked to oxidative stress (28,56).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In past work, using an executive memory task in younger POTS patients, we demonstrated that POTS patients exhibit a progressive cognitive impairment during step-wise incremental orthostatic stress (36). Moreover, cognitive impairment was associated with neurovascular uncoupling (35,52) such that the normal increase in CBF after neuronal activity (functional hyperemia) was absent in POTS patients (32,52). Neurovas- We have previously shown that POTS patients experience a deficit in NO-dependent vasodilation within the peripheral microcirculation, linked to oxidative stress (28,56).…”
Section: Discussionmentioning
confidence: 88%
“…One of the most debilitating symptoms of POTS is cognitive impairment (32,44), sometimes referred to as "brain fog" (43). In past work, using an executive memory task in younger POTS patients, we demonstrated that POTS patients exhibit a progressive cognitive impairment during step-wise incremental orthostatic stress (36).…”
Section: Discussionmentioning
confidence: 95%
“…Along with headache or vision problems, patients with CFS may experience cognitive and behavioral alterations. An excellent review by Ocon1 describes the ‘brain fog’ associated with CFS as slow thinking, difficulty focusing, lack of concentration, forgetfulness or haziness in thought processes. Clinically, reduced cerebral blood flow, increased activity in cortical/subcortical activation during mental tasks, deficits in processing information, impaired attention, and working memory are reported 1.…”
Section: Cns Findings In Cfsmentioning
confidence: 99%
“…Billeddiagnostiske og nevropsykologiske tester viser avvikende funn i sentralnervesystemet hos pasienter med CFS/ME (37)(38)(39)(40)(41)(42)(43) . «Sentral sensitisering» (utvikling av hypersensitivitet for ulike stimuli i sentralnervesystemet), kan vaere en mekanisme ved CFS/ME (44)(45)(46) .…”
Section: Utløsende Faktorerunclassified